2015
DOI: 10.1002/jcsm.12073
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia and mortality among a population‐based sample of community‐dwelling older adults

Abstract: BackgroundSarcopenia is a risk‐factor for all‐cause mortality among older adults, but it is unknown if sarcopenia predisposes older adults to specific causes of death. Further, it is unknown if the prognostic role of sarcopenia differs between males and females, and obese and non‐obese individuals.MethodsA population‐based cohort study among 4425 older adults from the Third National Health and Nutrition Survey (1988–1994). Muscle mass was quantified using bioimpedance analysis, and muscle function was quantifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
191
4
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 258 publications
(236 citation statements)
references
References 40 publications
(104 reference statements)
16
191
4
4
Order By: Relevance
“…The 'Low SPPB-scores' group have a fifty percent higher risk compared to the 'High SPPB-scores' group. These data of hospitalized geriatric patients confirm the results of other studies in different populations 4,10,13,15,[21][22][23] . Figure 1 gives an overview of the Kaplan Meier curves of all these significant class variables.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The 'Low SPPB-scores' group have a fifty percent higher risk compared to the 'High SPPB-scores' group. These data of hospitalized geriatric patients confirm the results of other studies in different populations 4,10,13,15,[21][22][23] . Figure 1 gives an overview of the Kaplan Meier curves of all these significant class variables.…”
Section: Discussionsupporting
confidence: 90%
“…Later research however, demonstrated that, besides skeletal muscle mass, also muscle strength and/or physical performance were important in the clinical specification of sarcopenia. Since then, a revolution in the concept of the definition of sarcopenia had been set [3][4][5] . Several international research groups, including the European Working Group on Sarcopenia in Older People (EWGSOP), use these three determinants to present their clinical definition for the diagnosis of sarcopenia 6,7 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sarcopenia is defined as loss of skeletal muscle mass accompanied by a reduction in muscle strength or physical performance,1 may be more severe among elderly individuals2 and patients with chronic disease such as those with chronic kidney disease (CKD) 3. There is no consensus regarding operational criteria for sarcopenia in patients with advanced pre‐dialysis CKD or maintenance hemodialysis.…”
mentioning
confidence: 99%